Millimeter waves in communication systems as a prospect for the development and application of robotic means and complexes - Vladislav R. Skrynskij (Физика волновых процессов и радиотехнические системы)
Background. Millimeter-wave communication systems are becoming more and more relevant in conditions of saturation of the low-frequency spectrum and growing requirements for data transmission speed. The high degree of radio wave absorption in the atmosphere creates unique opportunities for the formation of interference-proof wireless local and personal networks. These factors emphasize the need for in-depth study of the features and advantages of millimeter-wave band application in radio communications. Aim. The purpose of this study is to analyze the peculiarities of using millimeter waves in different types of radio communications, as well as to evaluate their advantages and disadvantages for the creation of high-performance communication systems, including robotics and 5G networks. Methods. The research used analysis and modeling methods aimed at studying the processes of attenuation, scattering and distortion of signals when radio waves propagate in the atmosphere. Adaptive frequency tuning was also evaluated to optimize the quality of communication depending on environmental conditions. The study covered various types of radio communications, including terrestrial, satellite and aircraft communications. Results. The results of the study showed that atmospheric absorption is significantly reduced at high altitudes where aviation wireless LANs and drone swarms operate. Adaptive frequency tuning has been demonstrated to be effective in providing reliable communication in various scenarios, which is critical for maintaining data transmission quality. For high-performance communication networks, including robotic systems, monolithic integrated circuits operating in the 50–90 GHz range with integrated antennas based on state-of-the-art technologies are required. Conclusion. Thus, millimeter waves represent a promising direction for the development of wireless networks, especially in the context of new commercial 5G networks. Higher millimeter-wave frequencies provide improved conditions for network connectivity in industry and robotics, which opens new horizons for the application of modern communication technologies. The need to increase the complexity of the electronics at each network node emphasizes the importance of further research in this area to achieve the high tracking and pointing requirements of directional links.